Subinertial hydrodynamics around a cape influenced by a western boundary current. (5th April 2021) - AlYousif, Ahmad; Laurel-Castillo, Jorge A.; So, Sangdon; Parra, Sabrina M.; Adams, Peter; Valle-Levinson, Arnoldo
Abstract: Subinertial hydrodynamics were investigated at an inner-shelf around a cape on the Florida Atlantic coast during spring 2014. The area to the northeast and southeast of Cape Canaveral was instrumented with four moored Acoustic Doppler Current Profilers (ADCPs) within the swales on either side of shoals. The purpose was to examine the influence of a western boundary current (WBC) on inner-shelf subinertial flow, which was mainly along the shelf. A Concatenated Hilbert Empirical Orthogonal Function (CHEOF) analysis showed that Mode 1, which accounted for 95.7% of flow variance, described variations in the along-shelf current. Wavelet coherence analysis was used to examine relationships between CHEOF Mode 1 and potential environmental forcings. Analysis of the cross-shelf momentum terms showed geostrophic balance throughout the deployment with occasional contribution of the gradient of the wave radiation stress S xx . Along-shelf momentum was beyond frictional, as other terms in the balance were also influential. When along-shelf winds and the Florida current are oriented in the same direction, an increase in Florida current transport is observed and vice versa. Enhancement of the Florida current is associated with an increased positive across-shelf sea surface slope in accordance with geostrophy, driving the inner-shelf subinertial flow in the same direction as the western boundary current (WBC). Conversely, southward along-shelf winds coincided with weakening of the Florida current and a negative inner-shelf sea surface slope that maintained geostrophy, driving a southward inner-shelf flow. Highlights: This study investigates the influence of the Florida current on subinertial hydrodynamics off a cape in an inner shelf. Statistical analyses were used to examine relationships between the subinertial flow and different environmental forcings. Cross-shelf momentum showed that subinertial flow was in geostrophy with occasional contribution of the gradient of S xx . The along-shelf momentum was beyond frictional. Results indicated that the Florida current had a clear influence on subinertial hydrodynamics through water-level slopes.